Effect of the Acid-Etching on Grit-Blasted Dental Implants to Improve Osseointegration: Histomorphometric Analysis of the Bone-Implant Contact in the Rabbit Tibia Model - Blanca Ríos-Carrasco (MDPI AG, 2021)
Previous studies have shown that the most reliable way to evaluate the success of an implant is by bone-to-implant contact (BIC). Recent techniques allow modifications to the implant surface that improve mechanical and biological characteristics, and also upgrade osseointegration. Objective: The aim was to evaluate the osseointegration in rabbit tibia of two different titanium dental implant surfaces: shot-blasted with Al2O3 (SB) and the same treatment with an acid-etching by immersion for 15 s in HCl/H2SO4 (SB + AE). Material and methods: Roughness parameters (Ra, Rt, and Rz) were determined by white light interferometer microscopy. Surface wettability was evaluated with a contact angle video-based system using water, di-iodomethane, and formamide. Surface free energy was determined by means of Owens and Wendt equations. Scanning electron microscopy equipped with X-ray microanalysis was used to study the morphology and determine the chemical composition of the surfaces. Twenty-four grade 4 titanium dental implants (Essential Klockner®) were implanted in the rabbit’s tibia, 12 for each surface treatment, using six rabbits. Six weeks later the rabbits were sacrificed and the implants were sent for histologic analysis. Resonance frequency analysis (RFA) was recorded both at the time of surgery and the end of the research with each device (Osstell Mentor and Osstell ISQ). Results: The roughness measurements between the two treatments did not show statistically significant differences. However, the effect of the acid etching made the surface slightly more hydrophilic (decreasing contact angle from 74.7 for SB to 64.3 for SB + AE) and it presented a higher surface energy. The bone-to-implant contact ratio (BIC %) showed a similar tendency, with 55.18 ± 15.67 and 59.9 ± 13.15 for SB and SB + AE implants, respectively. After 6 weeks of healing, the SB + AE showed an implant stability quotient (ISQ) value of 76 ± 4.47 and the shot-blasted one an ISQ value of 75.83 ± 8.44 (no statistically significant difference). Implants with different surface properties had distinctive forms of behavior regarding osseointegration. Furthermore, the Osstell system was an invasive and reliable method to measure implant stability. Conclusion: Both surfaces of implants studied showed high osseointegration. The SB and SB + AE implants used in our study had similar behavior both in terms of BIC values and RFA. The RFA systems in Osstell Mentor and Osstell ISQ confirmed nearly perfect reproducibility and repeatability.